Comparison of the Calf Thymus DNA Binding Interactions of 5-hydroxymethylfurfural and its Synthesized Derivative, 5, 5’[oxy-bis(methylene)]bis-2-furfural: Experimental, DFT and Docking Studies. (2023)
In this study, the in vitro DNA-binding interactions of the food/drug additive, 5-hydroxymethylfurfural (HMF) and its major degradant, 5, 5’[oxy-bis(methylene)]bis-2-furfural (OBMF) were investigated. OBMF was synthesized and characterized using IR, NMR and mass spectrometry. Photometric titrations revealed OBMF induced more extensive perturbations in the 258nm band of DNA and exhibited binding constants that were 5–12-folds higher than those of HMF. The greatest net changes in viscosity of DNA induced by HMF and OBMF were 10.5 and 8.9%, respectively which confirmed both compounds as minor groove binders. Docking revealed that OBMF and HMF bound to the guanine–cytosine regions of minor groove of DNA with global binding energies of −36.36 and −26.12 kcal/mol, respectively. DFT calculations revealed the higher electrophilicity of OBMF contributed to its increased interaction with the negatively charged DNA backbone. There is a need for stricter control of permissible levels of OBMF in food and drug products.